Pemetaan Informasi Sebaran Bidang Ilmu Pada Skripsi Fakultas Matematika dan Ilmu Pengetahuan Alam Lulusan IPB University Tahun 2015 - 2019 Berdasarkan Universal Decimal Classification: Suatu Kajian Bibliometrika - Raden Wahyudin; Abidin (Jurnal Pustakawan Indonesia, 2020)
Preliminary. IPB-University, a leading university in Indonesia, always produces a lot of research and innovation. Academic writing in the form of a thesis is a real proof. However, there has been no study that has mapped the results of these studies. This research was conducted to determine: the distribution of research topics, create a map of the field of science based on the Universal Decimal Classification standard, and visualize a map of keywords, as well as the productivity of the supervisor in the thesis of the Faculty of Mathematics and Natural Sciences, IPB University. Research Methods. This research is a bibliometric study with quantitative research methods, in order to describe the mapping of information on the distribution of knowledge in the thesis of the Faculty of Mathematics and Natural Sciences, IPB University. Research Data Processing. The object of this research is the Faculty of Mathematics and Natural Sciences thesis data in the IPB University Library database. The data is processed using the M.S. Excel and grouped according to the Universal Decimal Classification standard. The keyword data was created in an RIS File and analyzed using the VosViewer-Visualizing Scientific Landscapes 1.6.1.5 program developed by Nees Jan Van Eck and Ludo Waltman. Research Result. Proving that the thesis research topics of Faculty of Mathematics and Natural Sciences, IPB University graduates in 2015-2019 are 3,550 titles. Map of fields of science based on UDC showing research topics at most grade 004: “Computer Science and Technology, Computing and Data Processing” 719 (20.25%) titles, research topics at least grade 590: “Zoology” 43 (1.21%) . Co-word analysis using Vosviewer 1.6.1.5 on the occurrence of a minimum of 5 keywords succeeded in visualizing 683 keywords in 12 clusters. The keyword that appears the most occurs is "Computer Science and Technology" 153 times. Network Visualization shows the trend of the most popular research topics: “Computer Science and Technology” is in cluster 5 with a total network link strength of 397. Overlay Visualization shows a tendency the year the research was conducted, which was between 2016-2018. Density Visualization shows the tendency for the density of research volumes for each of these keywords to vary. The highest productivity of the thesis supervisor as the main supervisor is Imas Sukaesih Sitanggang as many as 79 guidance, while as member supervisors are Ali Kusnanto and Budi Waryanto, the number of guidance is 42 and 8 thesis guidance, respectively